SpO2/FiO2 ratio as a better metric for assessment of RBC transfusion effectiveness in non-traumatic critically ill patients with physiologic derangements - Tilendra Choudhary; Geoffrey Smith; John D. Roback; Ravi M. Patel; Cassandra D. Josephson; Rishikesan Kamaleswaran (PLoS ONE, 2025)
Identifying critically ill patients who are likely to improve their respiratory physiology following RBC transfusion is dynamic and difficult. Current decision tools are over-reliant on hemoglobin transfusion thresholds, without considering respiratory measures that may reflect physiologic effects of anemia and functional responses to RBC transfusion. Further, routine clinical measures to determine transfusion efficacy beyond hemoglobin increment are lacking to identify patients as responders or non-responders. We present a two-center retrospective cohort study aiming to determine a potential biomarker to assess the physiologic response of RBC transfusion for non-traumatic ICU patients. The study was performed with 13,274 eligible patients at the first center. Another 3,757 from the second center were used as a validation population. We introduced a comparative analysis of two respiratory measures, SpO 2 and SpO 2 /FiO 2 (SF) ratio, in addition to hemoglobin, to assess individual patient responses to RBC transfusion. A statistical study was performed to compare these markers before and after the transfusion interval. Based on quantitative statistical analyses, we found SF ratio to be a more effective biomarker than hemoglobin alone for revealing RBC transfusion efficacy. There existed an inverse correlation between pre-transfusion SF and transfusion efficacy. The results were consistent across both centers, revealing generalizability. With the SF data from both the centers, we also developed a random forest-based regression model that significantly evaluated the level of transfusion effectiveness ( p < 0.001).